Диаграммы плавкости солевых систем; Многокомпонентные системы: Справочник - Посыпайко В. И. Виктор Иосифович; Алексеева Е. А. Екатерина Александровна; Васина Н. А. Нина Алексеевна; Грызлова Е. С. Елена Сергеевна; Тарасевич С. А. Стелла Адольфовна; Попова И. Г. Ирина Григорьевна (Москва, Химия, 1977)
Авт. указ. на обороте тит. л.